OPTIMIZATION OF PHENOLIC COMPOUNDS IN ROBUSTA GREEN BEANS COFFEE THROUGH THE WET FERMENTATION PROCESS WITH THE RESPONSE SURFACE METHODOLOGY - Gunawan Wijonarko; Ike Sitoresmi mulyo Purbowati; Riyan Anggriawan; Ali Maksum (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Coffee is a refreshing drink that has potential as an antioxidant shown by its total phenol content. Fermentation is used to increase the phenolic compound content in coffee. The purpose of this study was to optimize the wet fermentation process to produce optimal phenolic compounds in green bean coffee. The process optimization was carried out by using Response Surface Methodology with three independent variables, namely the addition of yeast, added sugar, and fermentation time. The results of the quadratic model equation research to get the optimal process, namely Y= 65.18 + 0.56X1 + 2.66X2 + 16.26X3 + 1.51X1X2 + 0.18X1X3 + 0.66X2X3 + 9.29X12 + 23.71X22 + 6.08X32 with r2 of 0.8242 The optimum value of the wet fermentation process is based on the predictive value of the quadratic model, namely the addition of yeast 3.25%; added sugar 21.38%; and 124.73 hours of fermentation time resulted in a total phenol of 10.22 mg GAE / g.